Through the eye of a butterfly: Assessing biodiversity impacts of cashew expansion in West Africa. (November 2015) - Vasconcelos, Sasha; Rodrigues, Patrícia; Palma, Luís; Mendes, Luís F.; Palminha, Agostinho; Catarino, Luís; Beja, Pedro
Abstract: The cultivation of perennial cash crops is fast expanding in the tropics, but for most crops and regions there is very limited understanding about their biodiversity impacts. This is the case of cashew nut cultivation, which is occupying ever larger areas, particularly in West Africa. Here we investigated the impacts of cashew cultivation on biodiversity using butterfly assemblages sampled across a gradient of cashew expansion in Guinea-Bissau (West Africa). The overall species richness and abundance of butterflies were only slightly lower in cashew orchards than in native woodland habitats, but whereas the former were dominated by generalist species, the latter showed a much higher richness and abundance of trophic and habitat specialists. The landscape context significantly affected butterfly assemblages, with reduced richness and abundance of generalist species recorded within woodland habitats in heterogeneous landscapes with low woodland cover. Increases in land cover by cashew cultivation were associated with reduced abundance of specialist species within woodland habitats, and reduced abundance of generalist species within cashew orchards. Overall, our study provides the first evidence that cashew expansion may have serious negative consequences for biodiversity in West Africa, suggesting that this is an unfolding conservation problem that needs to be fully evaluated. Retaining woodland patches within production landscapes might help reducing the negative impacts of cashew expansion on biodiversity. Highlights: We compared butterfly assemblages between cashew orchards and native woodlands. Cashew orchards had slightly lower richness and were dominated by generalist species. Specialist species were much less diverse and scarcer in cashew orchards than in woodlands. The negative effects of cashew were stronger in landscapes with less woodland cover. Cashew expansion in West Africa may have serious negative impacts on biodiversity.